Analysis and improvement of the procurement process using process mining solution in a project-oriented organization - Elmira Darzi; Mehrdad Agha Mohammad Ali Kermani; Mostafa Jafari (مطالعات مدیریت کسب و کار هوشمند, 2023)
Due to their temporary nature and precise time and cost planning, project organizations are more involved in the relationship between data and operational processes, which requires the correctness of the actual processes of the organization. On the other hand, one of the essential issues for managing project-oriented organizations is its business process management, but due to the dynamic behavior and complexity of the nature of a project-oriented organization, identifying the processes through the traditional modeling of business process management is not reliable. The emerging solution to this problem is called "process mining." The paper introduces a framework that employs accurate process identification to measure the performance of business units relative to reality. This comprehensive framework undertakes the prerequisite steps of identification, including monitoring and cleaning the process-aware information systems' data to discover the process's current state and examine it from different perspectives based on the selected process. The primary purpose of this paper is to develop a framework for improving the P2P process in Chavosh Rah Company through process mining. The paper presents a framework to enhance the P2P process in project-oriented organization by implementing and extracting knowledge from the process, discovering unexpected and hidden relationships, and finding bottlenecks by employing process mining.